2014
DOI: 10.1089/bio.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

Fit for Purpose Frozen Tissue Collections by RNA Integrity Number-Based Quality Control Assurance at the Erasmus MC Tissue Bank

Abstract: About 5000 frozen tissue samples are collected each year by the Erasmus Medical Center tissue bank. Two percent of these samples are randomly selected annually for RNA isolation and RNA Integrity Number (RIN) measurement. A similar quality assessment was conducted during centralization of a 20-year-old tissue collection from the cancer institute, a 15-year-old liver sample archive (-80°C), and a 13-year-old clinical pathology frozen biopsy archive (Liquid Nitrogen). Samples were divided into either high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
4
40
0
Order By: Relevance
“…The majority of studies investigated the association between RNA quality, as measured by RIN and/or 28S/18S, and storage time17 18 21–23 25–30 and/or temperature 12 17–27 29 30. The findings overwhelmingly indicated that RNA quality and integrity were not affected by either measure, and that RNA was highly stable for several hours,12 17–19 22 25–28 30 including overnight at room temperature 12.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies investigated the association between RNA quality, as measured by RIN and/or 28S/18S, and storage time17 18 21–23 25–30 and/or temperature 12 17–27 29 30. The findings overwhelmingly indicated that RNA quality and integrity were not affected by either measure, and that RNA was highly stable for several hours,12 17–19 22 25–28 30 including overnight at room temperature 12.…”
Section: Resultsmentioning
confidence: 99%
“…Since the RNA integrity of several tissue types is not influenced by the freezing method 13 and morphology is not harmed, tissue banks may consider terminating the use of isopentane after further internal validation. However, for diagnostic purposes such as enzyme histochemistry on frozen sections of muscle biopsies, where optimal morphology is of crucial importance, it is still necessary to use isopentane for optimal results.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a previous study, while the authors acknowledge the preservation effects of isopentane on morphology, it was not found to be better than nitrogen with respect to RNA quality. 13 Small samples such as needle biopsies can suffer air drying artifacts that damage tissue morphology and possibly also compromise RNA. To minimize evaporation, clinicians often send small samples to the laboratory either on moist gauze or submerged in isotonic salt solution.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Our RIN values are similar to previously reported values for colon cancer tissue. 16,17 Whether tissue should be stored at -80°C or -140°C remains unclear. 13,23 We observed no adverse effects on RNA quality in fresh-frozen tissue after storage at -80°C for up to 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Four different quality groups can be distinguished based on the RIN result (RIN < 5: not reliable for downstream analysis, 5 < RIN < 6: reliable for RT-qPCR only, 6 < RIN < 8: reliable for RTqPCR and gene expression arrays, RIN > 8: high-quality RNA reliable for all downstream analyses). [15][16][17] …”
Section: Tissue Samplesmentioning
confidence: 99%